Tourists perception and opinion towards ecotourism development and management in Redang Island Marine Park, Malaysia - Yacob, Mohd Rusli; Radam, Alias; Samdin, Zaiton (Canadian Center of Science and Education, 2011)
Ecotourism establishment are the merging the environmental conservation and development. The environmental conservation approach is by recognizing the right and influence of people in biological valuable areas, more attention to human and biological preferences. The development approach was link with the environment to generate economic profitability in term of businesses and employment opportunities. This study analyzed the tourist perceptions and opinions towards ecotourism management and development in one of the famous island in Malaysia. The research addresses concentrating on four sections; analyses of tourists profiles and their characteristic of visit; tourists perceptions and opinions on ecotourism resource management; ecotourism resource maintenance; and tourists opinion on implementing of revenue collection. The personal interview has been made with a total of 298 representative respondents available were used in statistical analyses. The results found that tourists have different preferences against their profiles in term of ecotourism resource management and maintenance as well as on revenue implementation. The results provide useful implications on ecotourism resources management in marine park. It is possibly assists park management for their future improvement in managing ecotourism resources and developed integrated management plan of ecotourism development.